ANALISIS EFISIENSI WAKTU PELAYANAN LOADING UNLOADING BAGASI PESAWAT DI BANDARA ADISUTJIPTO YOGYAKARTA - , REINHARD AUGUSTA, Prof. Dr-Ing. Ir. Ahmad Munawar, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Ground Handling Company is a third party to the activities of the airports along with the airline and the airport managerial. It deals with the passenger baggage service. It is a challenge for ground handling company in Adisutjipto Yogyakarta to serve passengers that reach for almost 3 million people per year. This research will look at baggage service process in terms of time, such as how to obtain an effective and efficient baggage service from the check-in counter to to the aircraft, and vice versa. Surveys are conducted by collecting data related to the process above and then the obtained data will be processed. The data is analyzed by simulation using Microsoft Excel and SPSS software. The simulation results will then be used to describe the loading-unloading process, which similar to the real condition and the movement patterns of the baggage itself. Thus, researcher can provide the possibility of changes toward better. The results of the simulation can be used as a consideration for decision makers in Adisutjipto Airport Yogyakarta especially in relation with the effectivity and the efficiency of loading-unloading system.